2009
DOI: 10.3844/ajassp.2009.1502.1508
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Low Complexity Lossless Coding Algorithm for Medical Images

Abstract: Problem statement:Nowadays a large number of various medical images are generated from hospitals and medical centers with sophisticated image acquisition devices, the movement toward digital images in radiology presents the problem of how to conveniently and economically store, retrieve and transmit the volume of digital images. Thus digital image data compression is necessary in order to solve this problem. So in a wide range of medical applications such as disease diagnostic and during the compression proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…It was reported that the technique out-performs Huffman, JPEG-LL and lossless JPEG2000 by 10-40%. Ghare et al [6] introduced a lossless image coding algorithm based on pixel redundancy reduction and using 2 matrices of Gray Scale and Binary. The algorithm achieved a maximum compression ratio of 4.…”
Section: Fig1mentioning
confidence: 99%
“…It was reported that the technique out-performs Huffman, JPEG-LL and lossless JPEG2000 by 10-40%. Ghare et al [6] introduced a lossless image coding algorithm based on pixel redundancy reduction and using 2 matrices of Gray Scale and Binary. The algorithm achieved a maximum compression ratio of 4.…”
Section: Fig1mentioning
confidence: 99%
“…The main function of VTK is for image processing, computer graphics and visualization in scientific computing, especially for three-dimensional reconstruction of functions (such as surface rendering and volume rendering ability and powerful image processing capability) [5] . VTK graphics and visualization in the field of commonly used algorithm package into a class, users in visual development process does not need to consider the specific details, which can bring great convenience into research and development.…”
Section: Vtk's Basic Functionmentioning
confidence: 99%
“…But lossless scheme is reversible and this represents an image signed with the smallest possible number of bits without loss of any information thereby speeding up transmission and minimizing storage requirement. Lossless reproduces the original image without any quality loss [2].Medical imaging does not require lossy compression due to the following reason. The first reason is the incorrect diagnosis due to the loss of useful information.…”
Section: Introductionmentioning
confidence: 99%